ANALISIS PENGINDERAAN JAUH DAN PEMODELAN 3D FAULT FRACTURE DENSITY (FFD) DALAM PENENTUAN ZONA PERMEABILITAS PERMUKAAN DI WILAYAH PANAS BUMI GUNUNG TAMPOMAS, JAWA BARAT: REMOTE SENSING ANALYSIS AND 3D FAULT FRACTURE DENSITY (FFD) MODELING INTO DETERMINATION OF SURFACE PERMEABILITY ZONES IN MOUNT TAMPOMAS GEOTHERMAL AREA, WEST JAVA - Adi, Abizar; Haryanto, Agus Didit; Hutabarat, Johanes; Gentana, Dewi (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2021)
The area of Mount Tampomas which is located in Buahdua District, Conggeang District, and Tanjungkerta District, Sumedang Regency, West Java was chosen as the research area because it is predicted to have geothermal potential with the presence of geothermal manifestations such as hot springs. The presence of manifestations relates to permeable zones controlled by geological structures. The lineament of the ridge and valley was observed and analyzed using ASTER GDEM remote sensing imagery and Indonesia Earth Form map (RBI), scale 1:25.000. The purpose of the study is to find out the relationship between permeability and the presence of geothermal manifestations in the research area. Research method by conducting remote sensing and fault fracture Density (FFD) analysis using 3D micromine software modeling. Results of remote sensing analysis with irradiation angle of 0°, 45°, 90°, 135° and altitude 45° shows the main pattern of the ridge - valley lineament interpreted as a fault in the research area have a relatively northwest-southeast and northeast-southwest direction. Indications of geological structures in the field are shown by the morphology of valley-ridges, in some places has a steep slope that form the fault escarpment and triangular facet. The FFD analysis results in the research area have varying permeability classes shown by low FFD values (0.00–3.00 km-1), medium (3.00-6.00 km-1) and high (6.00–9.33 km-1). The geothermal manifestations appear in the permeability zone that have medium to high FFD values marked by orange and red colors. From 3D micromine software modeling of the permeability zone and plotting of hot springs on the surface, it is clear that the appearance of hot springs to the surface is facilitated by faults that develop in the research area.